2012
DOI: 10.1016/j.ijnurstu.2011.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Having to focus on doing rather than being—Nurse assistants’ experience of palliative care in municipal residential care settings

Abstract: Background: Palliative care should be provided, irrespective of setting to all patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 24 publications
12
111
0
Order By: Relevance
“…On the other hand, students obtained the lowest mean score on the reverse scored item 3 (i.e., "I would be uncomfortable talking about impending death with the dying person"). This finding may reflect feelings of poor confidence in self-efficacy, due to the perception of helplessness, which is often observed among nurses [6] .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the other hand, students obtained the lowest mean score on the reverse scored item 3 (i.e., "I would be uncomfortable talking about impending death with the dying person"). This finding may reflect feelings of poor confidence in self-efficacy, due to the perception of helplessness, which is often observed among nurses [6] .…”
Section: Discussionmentioning
confidence: 86%
“…A recent study reported that nurse assistants often described palliative care as a contrast to the everyday care they performed, in that they had a concrete possibility to provide the care the patient's needed [6] . Moreover, the study emphasized that nurse assistants felt uncomfortable talking about death with patients or with their relatives and that they needed help to address their own emotions [6] . Taken together, these results seem to suggest that an excellent care may not always be provided to dying patients and that the patients may have unmet needs.…”
mentioning
confidence: 99%
“…In order to meet patients' needs to express existential concerns, nurses have been found to develop relationships of trust through effective communication skills (Mok and Chiu, 2004;Johnston and Smith, 2006). Alternatively, assistant nurses find it unnatural to talk about death with patients or their relatives and report that caring for dying patients provokes negative emotions (Beck et al, 2011). A study among healthcare staff at nursing homes found that they expressed a fear of death.…”
Section: Introductionmentioning
confidence: 99%
“…It was important to NAs that supervisors provided both personal and professional support (Beck et al, 2012;Cooper & Mitchell, 2006;Dellefield, 2008;Eriksson & Fagerberg, 2008). Support was often operationalized by NAs as hands-on assistance during direct resident care (Burke et al, 2001;McGillis Hall et al, 2005;Rubin et al, 2009).…”
Section: Supervisors Provide Support Resources and Informationmentioning
confidence: 99%